2006
DOI: 10.1007/11815921_59
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Spectral Band Selection/Extraction Techniques for Spectral Data

Abstract: Abstract. In the past few years a variety of successful algorithms to select/extract discriminative spectral bands was introduced. By exploiting the connectivity of neighbouring spectral bins, these techniques may be more beneficial than the standard feature selection/extraction methods applied for spectral classification. The goal of this paper is to study the effect of the training sample size on the performance of different strategies to select/extract informative spectral regions. We also consider the succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Moreover, transforms that decompose 2D contours which have different properties when compared to the Fourier transform can be investigated (e.g., the wavelet transform). To address the exhaustive combination of sets for descriptor selection, we plan to make use of methods for feature selection [23] or spectral band selection [28] that exist in the literature. Finally, we obtained improved results for the multi-class case by making use of a voting method, but even better results may be obtained with more elaborate coupling methods, e.g., by solving an optimization problem that takes into consideration the difference between the pairwise probability estimates [22].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, transforms that decompose 2D contours which have different properties when compared to the Fourier transform can be investigated (e.g., the wavelet transform). To address the exhaustive combination of sets for descriptor selection, we plan to make use of methods for feature selection [23] or spectral band selection [28] that exist in the literature. Finally, we obtained improved results for the multi-class case by making use of a voting method, but even better results may be obtained with more elaborate coupling methods, e.g., by solving an optimization problem that takes into consideration the difference between the pairwise probability estimates [22].…”
Section: Discussionmentioning
confidence: 99%
“…While the coarse spectral resolution of imaging instruments such as Landsat-TM, ETMþ, ASTER, SPOT-HRV, IRS-LISS limits the ability to distinguish and map finer spectral differences of materials, very narrow spectral resolution coupled with large number of spectral bands significantly reduces the efficiency and accuracy of spectral analysis methods for material mapping. Consequently, numerous studies have reported the selection of optimal spectral bands as a compromise solution for an efficient processing of hyperspectral data for material mapping (Karlholm and Renhorn, 2002;Skurichina et al, 2006;Melendez-Pastor et al, 2008). Furthermore, the majority of the current generation hyperspectral imaging systems (eg, AVIRIS, HyMAP, DICE, CASI) acquires spectral data at a spectral resolution of 10-20 nm with variable sampling intervals, thus requiring the resampling of the finer resolution spectral libraries to match to that of the hyperspectral image under consideration.…”
Section: Optimal Spectral Resolution/sampling Intervalmentioning
confidence: 99%
“…Since which spectral band selection technique is preferred seems to be defined by the problem [5], we study the performance of 7 different band selection strategies, applied for spectral classification of seismic events at Nevado del Ruiz volcano. We compare these results with those obtained without any dimensionality reduction, i.e.…”
Section: Introductionmentioning
confidence: 99%